Finanças públicas de Goiás: comportamento da arrecadação e análise da causalidade entre receitas e despesas (2002/2011) - Seixas, Flávio Henrique de Sarmento (2012)
This present dissertation analyzes the performance of public accounts of Goiás during 2002/2011. There were two main problems treated: first, from the fact that the total tax revenue surpassed, in good measure, the significant economic growth in the region, it was investigated the causes for such performance. Additionally, was analyzed what kind of behavior occurred in the intertemporal Goiás revenue and expenditure relationship, so that such a relationship may or may not justify budgetary imbalances occurred during the period or that would compromise the ongoing fiscal adjustment. Such analysis allows to compare the results of Goiás with those obtained in other studies that, in general, fit the majority of Brazilian states as having performed fine adjustment, much as the volume of transfers from the Union that, properly, for their autonomous capacity to tax and collect. The results of Goiás indicated a relative strength of independent taxation, arising from the total revenue from its main tax (ICMS), but occurred much because of the tax effort reflected in the subgroups Debt and Fiscal Action, accompanied by an increasing transfers government volume and a greater proportion than 20% of total revenue in the period. Added to this set, the long cycle of the regional economy and positive force that provided the spontaneous collection of ICMS, however, the intensity lower than that cited in the subgroups. On the other hand, contributed to the fiscal results obtained for the answer the second research problem: the intertemporal relationship between revenues and expenditures for the state in the period indicated a strong tendency to fiscal synchronization, which allowed at least ease the fiscal situation worse when the state was in the recent past.